National Land Law Reform in Facing Globalization - Darwin Ginting (UBL, 2013)
Problem of land is a national problem, it is our problems. It is not just agroup interest. It means thatproblem of land is very fundamental for our country because land has a political dimension and is verystrategic as a means of unifying a nation.Most problems of land which have been faced nowadays can make disorder, legal uncertainty,injustice among people, so there should be a pro-active effort to accelerate the achievement of nationalgoals in the field of land and agrarian. This research is descriptive-analytic and uses juridical-normativeapproach, history of law, and juridical-qualitative analysis. From the result of this research, it can beconcluded that the efforts of NationalLand Law Reform are required through the Land Act, because thisAct is hoped to be able to solve the land and agrarian problems all over Indonesia. At least, The Land Actis supposed to pay attention to right to control the State, communal land right, nationalism, rights of land,management right, restriction on ownership and control of land, social function on land, settlement ofland dispute, ministry level institution, unification and land law pluralism, and pay attention toglobalization demand.